THE EFFECTIVENESS OF CONSUMING MORINGA LEAF PUDDING TO PREVENT STUNTING AMONG CHILDREN AT PAUD ADELWEIS IN WEST CIKARANG, BEKASI DISTRICT IN 2023 - Fitri Aini Sujadalillah; Marni BR Karo (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
Stunting is a global health problem affecting 165 million children around the world. The prevalence of stunting in Indonesia reached 21.6% in 2021. Four children were identified as stunted (12.1%), and 29 were normal (87.9%) in PAUD Adelwais in March-April 2023. Moringa leaves are one intervention that can be used to prevent stunting. Moringa oleifera (Moringa plant) is a widely and easily cultivated plant in Indonesia with the potential to be an ergonomic, cheap, and nutritious supplemental food. Many communities have widely used Moringa plants. The research aimed to determine the efficacy of Moringa leaf pudding in preventing child stunting. A quasi-experimental one-group pre-test and post-test approach was used as the research design. A total sample of 33 children were selected as respondents to the survey. The research results show that the consumption of Moringa leaf pudding effectively increases the height and weight of the children significantly, with a p-value of 0.000 ( 0.05). However, there was no statistically significant change in the body mass index with a p-value of 0.310 ( 0.05). There is a decrease in the prevalence of stunting in the PAUD Adelwais children, which decreased to 2 children (6.1%). Conclusion: Pudding with Moringa leaves is an effective intervention for preventing stunting in children.